Does the Brush-Sign Reflect Collateral Status and DWI-ASPECTS in Large Vessel Occlusion? - Rascle, Lucie; Bani Sadr, Alexandre; Amaz, Camille; Mewton, Nathan; Buisson, Marielle; Hermier, Marc; Ong, Elodie; Fontaine, Julia; Derex, Laurent; Berthezène, Yves; Eker, Omer Faruk; Cho, Tae-Hee; et al. (Frontiers in Neurology, 2022)
Introduction: The relevance of the brush-sign remained poorly documented in large vessel occlusion (LVO). We aimed to assess the relationship between the brush-sign and collateral status and its potential impact on baseline diffusion-weighted imaging–Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) in acute ischemic stroke (AIS) patients eligible to mechanical thrombectomy (MT). Methods: Consecutive patients admitted in the Lyon Stroke Center with anterior circulation AIS due to intracranial internal carotid artery (ICA) and/or M1 or M2 segment of the middle cerebral artery (MCA) occlusion eligible for MT were included. The brush-sign was assessed on T2-gradient-echo MRI. Collateral status was assessed on digital subtraction angiography according to the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR) score. Results: 504 patients were included. 171 (33.9%) patients had a brush-sign. Patients with a brush-sign more frequently had a poor collateral status (72 (42.1%) vs 103 (30.9%); p=0.017). In univariable analysis, a DWI-ASPECTS<7 was associated with a brush sign. Following multivariable analysis, the brush-sign no longer affected DWI-ASPECTS<7 while the latter remained associated with a younger age (OR 0.97, 95% CI 0.96-0.99), male sex (OR 1.79, 95% CI 1.08-2.99), a higher National Institutes of Health Stroke Scale (NIHSS) score (OR 1.16, 95% CI 1.10-1.21), a poor collateral status (OR 9.35, 95% CI 5.59-16.02), MCA segment (OR 2.54, 95% CI 1.25-5.38) and intracranial ICA (OR 3.01, 95% CI 1.16-8.00) occlusion. Conclusions and relevance: The brush-sign may be a marker of poor collateral status but did not independently predict a lower DWI-ASPECTS.